Vers l'égalité, ou au-delà ? Essai sur l'aube du socialisme - Frobert, Ludovic (Gouvernement en question(s), 2021)
How should socialism articulate the two exigencies which have always defined it: "to each according to his needs" and "to each according to his merits"? This short essay proposes to look back at its origins. In one of his beautiful turns of phrase, Pierre Leroux wrote, "Socialism appears, and the dawn of day is 1830". Proceeding here from a few portraits, notably those of Louis Blanc and Constantin Pecqueur, François-Vincent Raspail and George Sand, this essay shows how in this period of genesis, which even invented the term "socialism", the exigency of need was seen as the guiding principle. Far from being denied, merit nevertheless remained associated with this exigency. Already in those times of the first liberal waves, this original articulation allowed socialism to identify itself first, then to resist and finally to create, both in the field of ideas and that of experimentation, new paths to emancipation and social, economic and political progress. This option consisting in resolutely placing the wager of socialism beyond mere equality of opportunity, however rigorously defined it may be, therefore deserves to be recalled and reconsidered today.